Melanchton's portraits: interactions between visual image and narrative characteristics - Котляров П. (Видавничо-поліграфічний центр "Київський університет", 2015)
Until today there are still some ardent discussions about the role of Philip Melanchthon in the German Reformation and about his connections with the Humanism. We have made an attempt to analyze these relationships on the basis of visual sources and narratives which accompanied the images to answer the following question: how was Melanchthon perceived by his contemporaries? All XVI century portraits of Melanchthon made as engravings testify that in contrast to Martin Luther, who was always depicted as a reformer, and whose portrait has became a basis for a new Lutheran iconography, Melanchton was depicted as a humanist. Albrecht Dűrer was first to lay the foundations of the Melanchthon's humanist iconography in the engraving dated 1526. The peculiarity of this engraving was following: despite Malnchthon's religious activities in 1520s which accentuated his reformer side of personality, the portrait bears no indications of it. Reconsidered by Dűrer the image of Melanchthon as a humanist was copied and reproduced by other artists. Engravings made by different German artists were always accompanied by explanatory narratives which pointed to Melanchthon as humanist, scholar and teacher. The proposed engravings prove that educated elite regarded Melanchthon not only as a reformer but as a humanist. This image was reproduced to the great extent and so accepted by wide sections of the population.

У світовій історіографії до сьогоднішнього дня продовжуються дискусії щодо ролі Філіпа Меланхтона у німецькій Реформації та його зв'язках із гуманізмом. Нами була здійснена спроба, на основі візуальних джерел та супроводжуючого гравюри авторського наративу, розглянути це питання в іншій площині: уточнити, в якості кого сприймався Меланхтон його сучасниками? Досліджувані у якості візуального джерела портрети Меланхтона, виконані у техніці гравюри XVI ст., свідчать, що на відміну від Мартіна Лютера, який завжди зображувався в образі реформатора і портрет якого став основою для формування нової лютеранської іконографії, портрети Меланхтона наповнені у більшості гуманістичною риторикою. Основу складання гуманістичної іконографії Меланхтона поклав А.¸Дюрер, який першим зафіксував образ Меланхтона у гравюрі (1526 р.). Особливістю цього зображення було те, що попри релігійні практики Меланхтона у 20-х роках, що позиціонували його цілком як реформатора, розглядуваний портрет не несе жодних вказівок на реформаційну діяльність. Переосмислений Дюрером образ був підхоплений і закріплений у гравюрах інших художників. При цьому гравюри супроводжувалися пояснювальним наративом, що вказував на Меланхтона як гуманіста, вченого і педагога. Розглядувані гравюри доводять, що освічені верстви населення вбачали у Меланхтоні не лише реформатора, але й у більшій мірі – гуманіста.
Портрети Меланхтона: співвідношення візуального образу і наративних характеристик
Keywords: Melanchthon; the Reformation; the Humanism; engraving; portrait; Меланхтон; Реформація; гуманізм; гравюра; портрет